Ex-post service contract performance management. (2019) - Forbes, Brian; Brady, Malcolm
This paper highlights how contract incompleteness can threaten the performance of public procurement facilities management contracts during their implementation stages, based on a multiple case study comprising five public procurement services contracts. The paper takes a principle-agent view and with the unit of analysis being the contract itself. The paper shows that contract contingencies are almost inevitable and may stem from the written contract or from the participating organisations. Written and unwritten contract management mechanisms were used in practice to deal with contingencies as they arose in the services case studies examined. The paper found that written contracts do not always provide satisfactory remedies for unexpected contingencies. Ex-post mechanisms were used to manage the contract including incentives, information systems and signals. Time, resource or position signals were used in all five cases and provided an effective mechanism to manage unexpected contingencies in written contracts that proved to be incomplete.